Perancangan Sistem Informasi Koperasi Simpan Pinjam Institut Bisnis dan Informatika Kwik Kian Gie Berbasis Microsoft Access 2013 dan Hypertext Preprocessor (PHP) - Elis Sondang Dasawaty (Jurnal Informatika dan Bisnis, 2014)
This study used a qualitative descriptive study based on case studies that describe the real stateof the subject under study. Data collection methods used in this study was the observation andstudy of literature as a basis deductive hypotheses.This design results in the form of documents used in this study is a document of cooperativeemployees Institute of Business and Information Kwik Kian Gie. Based on the collection of datafrom documents obtained then analysis of needs (requirements definition) are in need is, CreditUnions reports every month, reports member savings. Where members can see the rest of theloan see the rest of the loan. The conclusion of this paper is the Savings and Loans CooperativeInformation Systems KSB was made to facilitate borrowing and saving view data members. Byusing this system work load becomes lighter because all done in a computerized process. Thusfurther improved the performance of cooperatives.